Occupational Health and Safety Culture is Associated with Unsafe Behavior in Airline X Airside Workers at I Gusti Ngurah Rai International Airport Denpasar - Juli Ariawan, I Ketut; Kerta Duana, I Made; Sri Nopiyani, Ni Made (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Workplace accidents among airside workers—such as being struck by luggage—remain common in the aviation industry. Unsafe behavior is often influenced by the occupational health and safety (OHS) culture adopted by workers. Objective: This study aimed to examine the association between OHS culture perception and unsafe behavior among airside workers of Airline X at I Gusti Ngurah Rai International Airport, Denpasar. Method: A cross-sectional study was conducted from December 2022 to January 2023 using a self-administered questionnaire. The sample consisted of 98 airside workers from the Lion Air Group, selected through total sampling. Variables measured included OHS culture, top management commitment, OHS rules and procedures, communication, worker competence, involvement, and work environment. Data were analyzed using simple and multiple logistic regression. Results and Discussion: A total of 32.7% of workers had a poor perception of OHS culture, and 52% exhibited unsafe behavior. Multiple logistic regression showed that OHS rules and procedures (AOR=7.59; 95% CI=1.4–44.75; p=0.013) and worker involvement (AOR=31.54; 95% CI=6.61–150.37; p<0.001) were significantly associated with unsafe behavior. Conclusion: Strengthening OHS rules and encouraging active worker involvement are essential strategies to reduce unsafe behavior among airside workers in the aviation sector